Plan, prepare and connect: How investing in understanding and tracking the evolving needs of online students informs the development of targeted programs for transition and success - Horvath, Deanna; Stirling, Emma; Bevacqua, John; Coldrey, Michael; Buultjens, Phil; Buultjens, Melissa; Larsen, Amy (Journal of University Teaching and Learning Practice, 2019)
Growth in online higher education offerings has been significant in recent years, with many Australian Universities launching programs to extend into new markets and meet the student demand for greater flexibility in delivery modes. Further, it is well understood that good support is an essential component to student success, satisfaction and retention. Despite this, orientation, including non-academic support, is often overlooked in online education systems. Therefore, the current study aimed to develop an orientation program to increase student preparedness and facilitate ongoing support, in addition to developing evidence-based best-practice strategies to support academic’s when developing new online courses.